Pelatihan Pengembangan Keterampilan Komunikasi Visual Berbasis Photoshop Pada Karang Taruna Aksara Rw17 - Galih Whendasmoro, Raditya; Fauziyah (HIMPUNAN DOSEN GEMILANG INDONESIA, 2022)
The development of applications in the field of information technology has a great impact on various areas of life, one of which is the creative industry. Now there is a shift in the trend of obtaining information from conventional (offline) such as print media to digital media (online), so these skills are needed. This community service activity is in the form of graphic design training using adobe Photoshop application to Karang Taruna Aksara RW07 Pancoran Mas Village - Depok. This community service activity aims to help the youth of Karang Taruna Aksara RW07 in improving knowledge and skills on how to make designs in the form of making banners, brochure, and logos using the Adobe Photoshop application so that participants can compete, meet the needs of employment and can be entrepreneurial. This service activity is carried out by the method of delivering material about the substance of the activity, followed by the practice of operating Adobe Photoshop using a computer and evaluating the participants to find out to what extent they absorb the training material that has been given. Based on the results of graphic design skills training activities, it is known that participants can understand, and use the tools in Adobe Photoshop as well as design banners, logos, business cards, invitations, and edit photos well. Keywords: Training; Graphic Design; Photoshop; Skills; Karang Taruna